Relación de comprensión lectora y logro de aprendizaje del área de comunicación en estudiantes del cuarto grado de primaria en la institución educativa N° 60993, Belén 2023 - Torres Huali, Lisette Yadhira (2025)
The main objective of this study was to examine the relationship between reading comprehension and academic achievement in communication in 4th grade elementary school students. Using a non-experimental quantitative approach. It adopts the quantitative research approach and descriptive correlational design. The study population consisted of 110 students in the 4th grade of elementary school and an exhaustive study was carried out since the entire population was considered as a sample. The results of the survey revealed a positive and low correlation, confirmed by a Spearman Rho coefficient of 0.393 and an approximate significance of 0.000 (p < 0.01), interpreting that reading comprehension has a positive, albeit moderate, effect on academic achievement. However, the study revealed a moderate to high positive association (Spearman's Rho =0.772) between reading comprehension and proficiency: communicates orally in the area of Communication in fourth grade students. This suggests that improving reading comprehension can have a significant positive impact on Oral Expression.